Screening for eukaryotic motifs in Legionella pneumophila reveals Smh1 as bacterial deacetylase of host histones. Issue 1 (31st December 2022) - Herbel, Stefanie M.; Moyon, Lambert; Christ, Marvin; Elsayed, Eslam M.; Caffrey, Brian E.; Malmsheimer, Silke; Grin, Iwan; Hoffmann, Kerstin; Surmann, Kristin; Blankenburg, Sascha; Jung, Anna Lena; Herkt, Christina E.; et al.
ABSTRACT: Legionella pneumophila ( L.p .) is a bacterial pathogen which is a common causative agent of pneumonia. In humans, it infects alveolar macrophages and transfers hundreds of virulence factors that interfere with cellular signalling pathways and the transcriptomic landscape to sustain its own replication. By this interaction, it has acquired eukaryote-like protein motifs by gene transfer events that partake in the pathogenicity of Legionella . In a computational screening approach for eukaryotic motifs in the transcriptome of Legionella, we identified the L.p . strain Corby protein ABQ55614 as putative histone-deacetylase and named it "suppressing modifier of histones 1" (Smh1). During infection, Smh1 is translocated from the Legionella vacuole into the host cytosol. When expressed in human macrophage THP-1 cells, Smh1 was localized predominantly in the nucleus, leading to broad histone H3 and H4 deacetylation, blunted expression of a large number of genes ( e.g . IL-1β and IL-8), and fostered intracellular bacterial replication. L.p . with a Smh1 knockdown grew normally in media but showed a slight growth defect inside the host cell. Furthermore, Smh1 showed a very potent histone deacetylation activity in vitro, e.g . at H3K14, that could be inhibited by targeted mutation of the putative catalytic center inferred by analogy with eukaryotic HDAC8, and with the deacetylase inhibitor trichostatin A. In summary, Smh1 displays functional homology with class I/II type HDACs. We identified Smh1 as a new Legionella virulence factor with a eukaryote-like histone-deacetylase activity that moderates host gene expression and might pave the way for further histone modifications. IMPORTANCE Legionella pneumophila (L.p.) is a prominent bacterial pathogen, which is a common causative agent of pneumonia. In order to survive inside the host cell, the human macrophage, it profoundly interacts with host cell processes to advance its own replication. In this study, we identify a bacterial factor, Smh1, with yet unknown function as a host histone deacetylase. The activity of this factor in the host cell leads to attenuated gene expression and increased intracellular bacterial replication.